MicroRNAs : An Emerging Player In Autophagy - yongfei yang; CHENGYU LIANG (ScienceOpen Research, 2014)
Autophagy is an evolutionarily conserved self-digestion process for the quality control of intracellular entities in eukaryotes. In the past few years, mounting evidence indicates that microRNAs (miRNAs)-mediated post-transcriptional regulation of gene expression represents an integral part of the autophagy regulatory network and may have a substantial effect on autophagy-related physiological and pathological conditions including cancer. Herein, we examine some of the molecular mechanisms by which microRNAs manipulate the autophagic machinery to maintain cellular homeostasis and their biological outputs during cancer development. A better understanding of interaction between microRNAs and cellular autophagy may ultimately benefit future cancer diagnostic and anticancer therapeutics.